Microbial abundance, activity and population genomic profiling with mOTUs2 - Milanese, Alessio; Mende, Daniel Richard; Alves, Renato; Huerta-Cepas, Jaime; Bork, Peer; Zeller, Georg F.; Sunagawa, Shinichi (Nature Communications, 2019)
Metagenomic analysis based on universal phylogenetic marker gene (MG)-based operational taxonomic units (mOTUs) is a useful strategy, especially for microbial species without reference genomes. Here, the authors develop mOTUs2, an updated and functionally extended profiling tool for microbial abundance, activity and population profiling.